FASILITAS PENUNJANG REST AREA DESA WIRU : SEBUAH USULAN DESAIN - Pramesti, Previari Umi; Susanti, Riza; Ramandhika, Mirza (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2021)
The purpose of this community service activity is to provide a proposed design for the Wiru Village Rest Area Support Facility, Bringin District, Semarang Regency. This Rest Area Supporting Facility is a solution to the potential that can be optimized from Wiru Village as a village located on the alternative route of Central Java-East Java. The design proposal is prepared by mapping the strengths and weaknesses of the village conditions, then a SWOT analysis is carried out to formulate the ideal design. This rest area is not only expected to be able to facilitate road users, but also to raise the economic level of the village by optimizing the potential of the village. The design proposal is in the form of a 3-dimensional image which is expected to be a reference in the development process.